Estudo da flotabilidade e carga superficial da wollastonita na presença deamina e ácido oléico - Ana Paula Martins Soares (2015)
Wollastonite is a calcium silicate that is widely used in The United States and Asia mainly as a corrective of soil properties for agriculture, in manufacturing of high-strength concrete, in ceramics industry and as a substitute for asbestos, which is very harmful to human health. In Brazil, this use is dependent on imports and still incipient when related to the agricultural and civil construction potential recognized in the country. The possibility of selective flotation of Brazilians wollastonite, emphasizing the recent deposits discovered in Goiás, would increase significantly the prospects of industrial use of this mineral. Furthermore, the academic reference on the subject is yet unexplored and uncompleted and the flotation process is not yet used to concentrate wollastonite of Brazilian deposits due to inherent difficulties in the selectivity on the separation of wollastonite from others silicates which comprise the ore, among other facts. In this context, this work aimed to know in detail the zeta potential behavior and the flotability of wollastonite and diopside with amine and oleic acid in order to enable the selective flotation of these minerals. Also, compare the results with the main accessory minerals of wollastonite (calcite, quartz and feldspar). The results indicated the possibility of selective flotation of wollastonite relative to diopside using sodium oleate between pH 7 and 8. Other selectivity windows identified consider calcite separation from wollastonite using dodecylamine around pH 6, calcite separation from wollastonite using sodium oleate around pH 10 and microcline separation from wollastonite using dodecylamine around pH 3.